Targeting Calcium Release–activated Calcium Channel Is Not Sufficient to Prevent Rejection in Nonhuman Primate Kidney Transplantation. Issue 5 (May 2020) - Kwun, Jean; Ezekian, Brian; Manook, Miriam; Park, Jaeberm; Yoon, Janghoon; Freischlag, Kyle; Song, Mingqing; Farris, Alton B.; Sloan-Lancaster, Joanne; Fortier, Caroline; Rao, Patricia E.; Knechtle, Stuart J.
Abstract : Background: Calcineurin inhibitors successfully control rejection of transplanted organs but also cause nephrotoxicity. This study, using a rhesus monkey renal transplantation model, sought to determine the applicability of a new immunomodulatory drug inhibiting the store-operated calcium release–activated calcium channel of lymphocytes to control transplant rejection without nephrotoxicity. Methods: Animals underwent kidney transplantation and were treated with tacrolimus alone (n = 3), a CRACM1 inhibitor (PRCL-02) (n = 6) alone, or with initial tacrolimus monotherapy followed by gradual conversion at 3 weeks to PRCL-02 alone (n = 3). PRCL-02 was administered via a surgically inserted gastrostomy tube BID. Results: Dose-related drug exposure in monkeys was established and renal transplants were then performed using PRCL-02 monotherapy. Oral dosing of PRCL-02 was well tolerated and resulted in suppressed T-cell proliferation in in vitro MLR comparable to animals in the tacrolimus control arm. Animals receiving tacrolimus monotherapy were e on day 100 without rejection. PRCL-02 monotherapy only marginally prolonged graft survival (MST = 13.16 d; group 2) compared with untreated controls. Animals treated initially with tacrolimus and converted to PRCL-02 monotherapy had a mean graft survival of 35.3 days which was prolonged compared with PRCL-02 monotherapy but not compared with the tacrolimus-treated group. Pharmacokinetic studies showed inconsistent drug exposures despite attempts to adjust dose and exposure which may have contributed to the rejections. Conclusions: We conclude that, in this nonhuman primate model of kidney transplantation, PRCL-02 demonstrated evidence of in vivo immunosuppressive activity but was inferior to tacrolimus treatment with respect to suppressing immune transplant rejection. Abstract : Supplemental Digital Content is available in the text.